Rectal Gastrointestinal Stromal Tumor (GIST): About a Rare and Unusual Case - Jallouli, Abderrahmane; Jarti, Mariama; Haida, Marj Zohour; El Bouatmani, Mouna; Errami, Adil Ait; Oubaha, Sofia; Samlani, Zouhour; Krati, Khadija (International Journal of Innovative Research in Medical Science, 2021)
Rectal gastrointestinal stromal tumors (GIST) are extremely rare, accounting for approximately 0.1% of all rectal tumors. Diagnosis is based on histological and immunohistochemical confirmation. We report the case of a 38-year-old patient with a rectal GIST revealed by chronic rectal bleeding associated with rectal tenesmus, abdominal pain with painful contractions and frequent evacuations evolving in a context of altered general state. Rectoscopy was used to visualize the tumor mass and to take biopsies; their histological and immunohistochemical study revealed a rectal location of a gastrointestinal stromal tumor. The extension assessment was negative. After discussion of the case in a multidisciplinary consultation meeting, management consisted of initially putting the patient on Imatinib given the large tumor size, the degree of local invasion and the location of the mass (lower rectum), with regular follow-up in order to schedule a less invasive surgical resection later. Despite the rarity of rectal GIST, early diagnosis is necessary to avoid progression to locoregional invasion complicating some surgical resections given the anatomical constraints of the pelvic region. Hence the interest of neoadjuvant therapy with tyrosine kinase inhibitors allowing in some cases a decrease in tumor volume, a regression of the degree of local invasion and a decrease in the morbidity of the surgery in order to improve the patient's quality of life.